Adiga's The White Tiger as World Bank Literature - Al-Dagamseh, Abdullah M (CLCWeb : Comparative literature and culture, 2013)
In his article "Adiga's The White Tiger as World Bank Literature" Abdullah M. Al-Dagamseh reads Aravind Adiga's novel within the context of global neoliberal capitalism, especially as radical neoliberal reforms took root in India in 1991. Al-Dagamseh argues that The White Tiger read as world bank literature provides critiques of the globally hegemonic discourses of success story narratives by exposing the contradictions of different, but overlapping facets of neoliberal ideology. Further, Al-Dagamseh demonstrates that the novel serves to reveal the contradiction between mythical global narratives and the reality and nature of "success" and "development" achieved through violence, crime, and destruction and posits that fictional representations of violence challenge hegemonic success story narratives and development projects which turn out to be disappointments, delusion, inequality, class/caste division, corruption, violence, and uneven geographical development.